If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + 2 = cx + -6 Reorder the terms: 2 + ax = cx + -6 Reorder the terms: 2 + ax = -6 + cx Solving 2 + ax = -6 + cx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + ax = -6 + -2 + cx Combine like terms: 2 + -2 = 0 0 + ax = -6 + -2 + cx ax = -6 + -2 + cx Combine like terms: -6 + -2 = -8 ax = -8 + cx Divide each side by 'x'. a = -8x-1 + c Simplifying a = -8x-1 + c Reorder the terms: a = c + -8x-1
| 3G+3=2(2G-1)-44 | | 4/5z+1/6=-1/5z+1/3 | | 3x+2x-32=x+x-2 | | -3x^2+9x-7=0 | | Xsquared+4=4x | | x/2+1/5x+x/3=31 | | 2.5(.08)+3=13.8 | | 3(2A+1)-16=5A+3 | | x/8=1000 | | 3x+4x-4= | | (2.3+n)+14= | | 2k(8-7)-4k=k+9 | | 40/.20 | | 4x=-0.5y-1 | | =(2y-1)(-y) | | f(5)=.25x | | 4x^2+100x-896=0 | | 1-4(x+2)=7x-18 | | -12x-10=4x+8 | | 3×1/9 | | -7x+-4=17 | | 2.5(.08)+3= | | 2/5z+1/6=-3/5z+1/3 | | -5(2-x)+1=4(3+x) | | -10=-9x-8/-10 | | -4n+2=n+7(-6-7n) | | 6-5(2x-3)=4x-7 | | 8x-11=3(x-7) | | T=1/4*36^1/2 | | x/3-x/6= | | 3x-15+9=10x | | .5(x-18)-5= |